Implementasi Model Pembelajaran Kooperatif Berbasis Game Board Card Untuk Meningkatkan Hasil Belajar Peserta Didik (Studi Pada Materi Pokok Sistem Organisasi Kehidupan) - Thya Enjely Ningsi; Rifda Nurhikmawati Arif (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Low student learning outcomes in Life Organization System material remain a persistent challenge in junior high school science education, often due to the abstract nature of the content and teacher-centered learning approaches. This study aims to determine the improvement of learning outcomes of seventh-grade students on the topic of Life Organization System through the implementation of a cooperative learning model based on Game Board Card. This research is a Classroom Action Research (CAR) conducted in three cycles. The research subjects were 30 students of class VII.5. Research instruments included learning outcome tests (pretest and posttest), and student worksheets (LKPD). Data were analyzed using descriptive statistics and the N-Gain test. The results showed an increase in the average learning outcomes from Cycle I (67.00), Cycle II (70.17), to Cycle III (73.50). The percentage of students achieving mastery increased from 44.0% in Cycle I, to 50.0% in Cycle II, and 66.7% in Cycle III. The N-Gain analysis yielded an average score of 0.33 in the moderate category. The cooperative learning model based on Game Board Card is proven to gradually improve student learning outcomes on the Life Organization System topic.